Web-based Environmental Reporting: Evidence from Listed Manufacturing Companies in Bangladesh - MD. ZAHEDUL ISLAM; MOURI DEY; MD. ZAHIDUL ISLAM CHOWDHURY JANNAT (Asian Journal of Accounting Perspectives, 2024)
Research aim: Businesses worldwide are attempting to exhibit accountability and efficacy in addressing the threat of severe environmental imbalances. Understanding the underlying issues responsible for environmental disclosures in digital media is essential to improve its status. This research investigates the environmental performance of manufacturing firms and evaluates the corporate governance factors that affect these disclosure practices. Design/ Methodology/ Approach: This research applies multinomial logistic regression to deduce the nature of the connection between environmental disclosures made public on the web on 71 disclosure aspects or issues and corporate governance by collecting information from the websites of 193 listed manufacturing companies. Research finding: The findings imply that board size, CEO duality, and foreign ownership have a major impact on web-based environmental reporting. Theoretical contribution/Originality: This study integrates legitimacy theory and agency theory to understand the importance of efficient corporate governance in disclosing environmental information, thereby mitigating information asymmetry and voluntarily meeting stakeholder expectations. Practitioner/Policy implication: Corporate governance may develop best practices to guarantee that the online platform of voluntary environmental reporting creates a credible environment for exposing information to end users, resulting in a more comprehensive evaluation of company prospects. Research limitation: This study focuses on specific corporate governance characteristics. Other predictors can be considered to ensure better practices, such as the number of board meetings, educational quality of board members, stakeholder activism, political intervention, industry-specific environmental policy, etc. Moreover, longitudinal studies could offer further insights into the relationship between governance and environmental reporting.